2021
DOI: 10.1136/jitc-2021-002958
|View full text |Cite
|
Sign up to set email alerts
|

Individualized genetic makeup that controls natural killer cell function influences the efficacy of isatuximab immunotherapy in patients with multiple myeloma

Abstract: BackgroundPhase IIb clinical trial with isatuximab (Isa)-lenalidomide (Len)-dexamethasone (Dex) showed an improved progression-free survival (PFS) in patients with relapsed or refractory multiple myeloma (RRMM), but the efficacy varied by patient. Antibody-dependent cell-mediated cytotoxicity (ADCC) by natural killer (NK) cells plays a crucial role in arbitrating antitumor activities of therapeutic-antibodies. We tested if patient-specific genetic makeup known to set NK cell functional threshold influence resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…Interestingly, the KIR3DL2 carrier patients in our cohort also had the FcγR3A V-allele, and, accordingly, exhibited greater ADCC efficiency than the KIR3DL2+ and FcγR2A F/F individuals. These data agreed with the findings described by Sun et al, that reported a higher NK cell-mediated cytolysis of Multiple Myeloma cells dependent on the mAb isatuximab in the presence of the KIR3DL2+, HLA-A3/A11+, and FcγR3A V markers ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the KIR3DL2 carrier patients in our cohort also had the FcγR3A V-allele, and, accordingly, exhibited greater ADCC efficiency than the KIR3DL2+ and FcγR2A F/F individuals. These data agreed with the findings described by Sun et al, that reported a higher NK cell-mediated cytolysis of Multiple Myeloma cells dependent on the mAb isatuximab in the presence of the KIR3DL2+, HLA-A3/A11+, and FcγR3A V markers ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…The functional interaction of KIR3DL2 with HLA-A3/11 is poorly studied, and this interaction is weaker than the other KIRs with HLA-C and HLA-B ligands ( Dohring et al, 1996 ). Since KIR3DL2 is a framework gene present in all individuals, the functional role of the receptor is arguably dependent on its interaction with HLA-A3/11 ( Sun et al, 2021 ). Although the mechanism of anti-SARS-CoV2 activity rendered by inhibitory KIR3DL2 + HLA-A3/11 + interaction is unclear, our results indicate that NK cell recognition through 3DL2 + HLA-A3 + interaction may trigger more robust NK cytolysis when HLA-A3 is presented with viral peptides ( Hansasuta et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The control samples were HLA typed using a commercially available Sequence-Specific Oligonucleotide hybridization kit (LABType ® SSO, One Lambda, Canoga Park, CA). We described the KIR genotyping ( Sun et al, 2021 ) and HLA genotyping protocols by NGS ( Kong et al, 2021 ) and SSO ( Sun et al, 2021 ) elaborately in our previous publications.…”
Section: Methodsmentioning
confidence: 99%
“…Trastuzumab mediates ADCC against HER2 overexpressing cell lines which is irrespective of the NK cell donor genotype KIR-ligand interaction [7] Phase IIb clinical trial including 57 patients with (RR)MM receiving Isatuximab-Lenalidomide-Dexamethasone combination, supported by in vitro cytotoxicity assays Most prolonged PFS with patients carrying KIR3DL2 + HLA-A3/11 + and FCGR3A 158 V polymorphism combination (Not due to education), which was recapitulated in in vitro ADCC assays. Suppressed NK cell ADCC with KIR2DL1 + HLA-C2 + interaction KIR-ligand interaction [46] In vitro study using NK cells expanded on K562-mbIL15-41BBL cells.…”
Section: Results Summarymentioning
confidence: 81%